Logic proves that time does not get faster or slower (the universe is not produced by the singularity big bang) - Xie Ling (Annals of Mathematics and Physics - Peertechz Publications, 2022)
I use the axiom that equal conditions must have the same result.  Axiom proves that no matter how the velocity of an object changes, the time of all objects remains unchanged and unified.  Time can be expressed as an eternal constant. Time belongs to the abstract concept of material attributes, and time is not a material concept. There is an abstract concept of uniform velocity in the universe (For example, the velocity of light wave in vacuum is constant "C"). According to the constant and uniform velocity of time, an important physical theory is proved: the universe is not produced by the singularity big bang. Mathematical classification code: 00A79;83F05;00A30;03A05;70A05;70F20;03A10;03F03.